Review of the Method of Valuation of the SDR : Initial Considerations. (Policy Papers; Policy Paper ;, 2015)
This paper lays out initial considerations for the quinquennial review of the method of valuation of the Special Drawing Right (SDR) currency basket. As in previous reviews, a key objective is to enhance the attractiveness of the SDR as an international reserve asset. In that context, the review will assess the currencies for SDR basket inclusion, currency weights, and the SDR interest rate basket. The paper takes as a starting point the conclusions of the last review in 2010 and the subsequent Board discussion of currency selection criteria in 2011. At the time of the last review, China met the gateway export criterion but the renminbi (RMB) was not included in the SDR basket as it was not judged to be freely usable, the second currency selection criterion. In light of the Board's broad support in 2011 for the existing legal framework, and since China continues to meet the export criterion, this paper discusses building blocks relevant for a future determination on whether to include the RMB in the basket under the existing criteria.